DINAMIKA DAN TERAPAN METODOLOGI TAFSIR KONTEKSTUAL - Abdul Muiz Amir; Ghufron Hamzah (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
This article focuses on the study of dynamics and the application of contextual interpretation methodologies, so that the Qur'an does not tend to only be understood as limited to literal meaning, as well as the scope of understanding the Qur'an is not only bound by place and time when it is revealed, so it rigid to apply to the present. Hermeneutic theory has been widely studied and developed by Muslim and orientalism, although the emergence of hermeneutic theory is accompanied by dynamics of difference, both pragmatically and historically, but these differences have become a motivation for academics to further develop these theories towards more good One form of development shown by the adoption of the theory of ma’na-cum-maghza initiated by Sahiron Syamsuddin can be an alternative and a solution to get out of literal and liberal claims in interpreting the Qur'an In this article the author includes one form of application of the hermeneutic theory ma’na-cum-maghza by exploring the meaning of QS. Al-Ma'un / 107: 1-7, to uncover the side of differences in textual (classical) interpretation and interpretation contextual, especially the social view of the understanding of the sura. The result is that QS, Al-Ma'un / 107: 1-7 is full of social meanings that are very closely related and have a reciprocal relationship between theological-normative meanings and social meanings expressed in the surah.